Perancangan Alat Bantu Memasukkan Gabah Ergonomis Ke Dalam Karung - Studi Kasus Di Penggilingan Padi Pak Santo - Pratama, Antonius Hari; Setiawan, Heri (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 1 (2020): Volume 6 No 1 Juni 2020DO - 10.24843/JEI.2020.v06.i01.p05, 2020)
Pak Santo's rice mill is a rice mill located in the village of Tegal Arum. The factory serves the drying process until the rice mill. In carrying out the work process, factory workers use traditional methods, ranging from drying to packaging. Productivity in the process of packaging unhusked rice placed in a sack still requires more than 60 second/sack in a sack containing 25 kg, so it is less efficient in working time. The use of old tools is considered to be less effective, comfortable, safety, healthy, and efficient. Workers’ body posture when packing rice activities is considered unergonomics to be unhealthy because it causes muscle fatigue in the left-right shoulder and back based on initial observations using the Nordic body map questionnaire. From this problem the researchers designed an ergonomic tool to insert rice into sack "Abakan Gadak" using Nigel Cross method. Abakan Gadak is ergonomically designed to reduce muscle fatigue which has an impact on improving the quality of workers’ health and increasing worker productivity through decreasing process working time. The form of Abakan Gadak resembles a wheelbarrow with a height of 170 cm, width of 60 cm, and length of 90 cm. Improving of unhealthy working postures using the REBA method with ergofellow software.The results of the study using Abakan Gadak can improve health by reducing the level of risk from working postures that were very hight (score 12) to moderate (score 6). Productivity increased through the average working time of loading grain into sacks deceased by 15.24%, from 69.75 second/sack to 59.12 second/sack. Costs incurred for making tools amounted to Rp. 1,540,900